2016
DOI: 10.1534/genetics.115.181438
|View full text |Cite
|
Sign up to set email alerts
|

Unique and Overlapping Functions of Formins Frl and DAAM During Ommatidial Rotation and Neuronal Development in Drosophila

Abstract: The noncanonical Frizzled/planar cell polarity (PCP) pathway regulates establishment of polarity within the plane of an epithelium to generate diversity of cell fates, asymmetric, but highly aligned structures, or to orchestrate the directional migration of cells during convergent extension during vertebrate gastrulation. In Drosophila, PCP signaling is essential to orient actin wing hairs and to align ommatidia in the eye, in part by coordinating the movement of groups of photoreceptor cells during ommatidial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 86 publications
(144 reference statements)
3
23
0
Order By: Relevance
“…Notably, frl knockdown caused ommatidial rotation defects, as previously reported ( Fig. 3C) (Dollar et al, 2016). Only knockdown of fhos or form3 caused a reduction of rhabdomere size (ANOVA: f = 42.62, df = (6,63), p < 0.0001) ( Fig.…”
Section: Form3 Regulates Actin Accumulation In Photoreceptorssupporting
confidence: 87%
See 2 more Smart Citations
“…Notably, frl knockdown caused ommatidial rotation defects, as previously reported ( Fig. 3C) (Dollar et al, 2016). Only knockdown of fhos or form3 caused a reduction of rhabdomere size (ANOVA: f = 42.62, df = (6,63), p < 0.0001) ( Fig.…”
Section: Form3 Regulates Actin Accumulation In Photoreceptorssupporting
confidence: 87%
“…Other formins do function in photoreceptors. Frl is required for planar cell polarity in developing eyes, a requirement recapitulated in our studies (Dollar et al, 2016) (Fig. 3D).…”
Section: Form3 Regulates Neuronal Actin Filamentssupporting
confidence: 77%
See 1 more Smart Citation
“…This constitutes a new role for the Frl/Fmnl formin since so far it has been mainly described as participating to the lamellipodia/filopodia formation 4144 . It would be interesting to know if, like in other systems, Frl is regulated by either Cdc42 41, 44, 45 or Rac1 46 to promote the persistent network assembly. Furthermore, it is likely that other formins participate to the persistent network assembly, especially in the germband since the lack of Frl (frl 59/59 ) only partially reduces the network density (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4b). The DAAM formin would constitute a first good candidate since it has been shown that DAAM and Frl cooperate during axon growth in the mushroom bodies of Drosophila 45 .…”
Section: Discussionmentioning
confidence: 99%